PENGEMBANGAN MEDIA AUGMENTED REALITY (AR) DALAM MENGAJARKAN GERAK TARI TOR-TOR PADA SISWA KELAS V SDN 29 PAYAKUMBUH - Sonia Erika Ullyartha Purba; Zariul Antosa; Zufriady (STKIP Subang, 2025)
This research aims to develop Augmented Reality (AR) based learning media inteaching Tor-Tor dance movements to fifth grade students of SDN 29Payakumbuh. AR technology allows visualization of dance movements in three-dimensional form that is interactive and realistic, so it is expected to improvestudents' understanding of the basic movements of Tor-Tor dance. The researchmethod used is Research and Development with the Four-D model (Define,Design, Develop, Disseminate). The results of material, language and mediaexpert validation showed that the developed AR media fell into the "very valid"category with an average percentage of 95.1%. The product trial results from theteacher's response were 83.2% and the product trial results from the student'sresponse were 84.54%. Based on the product trial evaluation results of teachersand students, the average that can be obtained is 83.87% with a very goodcategory. Then the N-Gain test was conducted to measure the effectiveness ofaugmented reality media on the ability of grade V students for Tor-Tor dancematerial by conducting post-tests and pre-tests, getting a result of 0.80 (80%).Based on the results of the n-gain test, the developed augmented reality media iseffective. The tests on teachers and students also showed positive results with ahigh level of readability, attractiveness, and effectiveness in increasing students'interest and understanding of Tor-Tor dance. Thus, the development of AR mediais considered feasible to be used as an innovation in learning cultural arts,especially traditional dance, and can be a reference for the development of othertechnology-based learning media.